Analysis of Physical Housing Environmental Factors on the Incidence of Acute Respiratory Infection (ARI) in the Working Area of Public Health Centers in Sarolangun Regency - Sumardi, Sumardi; Mega, Olfa; Suryono, Suryono (Rifa'Institute, 2026)
Introduction: The physical condition of the home environment is one of the factors that can influence the health of household occupants, particularly the occurrence of Acute Respiratory Infection (ARI). Ventilation, lighting, humidity, and indoor temperature that do not meet health standards can increase the risk of respiratory disorders. Objective: This study aims to analyze the relationship between physical housing environmental factors and the incidence of ARI in the working area of Public Health Centers in Sarolangun Regency. Method: This study used a quantitative approach with an observational cross-sectional design. The study population consisted of all ARI patients recorded in four Public Health Center working areas in Sarolangun Regency totaling 7,251 cases. The sample consisted of 379 respondents determined using the Slovin formula with a cluster sampling technique. Data were collected through observation of the physical condition of houses and environmental measurements using a lux meter, measuring tape, and a digital thermometer equipped with a hygrometer. Data analysis was conducted through univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using logistic regression. Results and Discussion: The results showed that bedroom ventilation, house lighting, humidity, and indoor temperature had a significant relationship with the incidence of ARI (p-value < 0.05). Multivariate analysis showed that humidity was the most dominant factor influencing the incidence of ARI with an odds ratio value of 7.107. Conclusion: Physical housing environmental factors are associated with the incidence of ARI in the working area of Public Health Centers in Sarolangun Regency, with household humidity as the most dominant factor influencing the incidence of ARI.